Book Chain : Incentivizing Actors in the Book Chain to Increase Availability of Quality Books for Children - World Bank Group (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund builds evidence on results-based financing in education, including by capturing operational lessons around its use. In the PRACTICE series, experts share their experience from working in the field to provide practical advice on how to apply results-based approaches to boost education outcomes. Reports in this series highlight key discussion points from REACH roundtables, backed by direct though anonymous quotes from participating experts to allow for frank discussion.